Malvin Z-chalcone: An unexpected new open cavity for the ferric cation - George, Florian (1999)
It is demonstrated that complexation between the ferric cation and the Z-chalcone of the naturally occurring anthocyanin malvin takes place in acidic aqueous solutions. The flexible open cavity of the Z-chalcone best fits the steric and electronic requirements of the ferric ion in water.